Spatial and temporal variations of rainy days and mean daily rainfall intensity in northern Nigeria. - OLADIPO , E. O.; SALAHU, S. (MAUSAM, 1993)
The spatial and temporal variations of rainy Gays arid daily rainfall intensity for northern Nigeria for using 54 years data are analysed, The extent and nature of non-random changes, such as trend and fluctuations are Investigated. In general, both, the rainy day frequency and mean daily rainfall intensity decreases northwards except for localized orographic effect in the north central Part of the region. There is statistical evidence or decreasing trend in the, number of rainy days over the period of study, but the trend analysis showed no significance or the mean daily rainfall intensity. This suggests that the recent decreasing rainfall trend In the region particularly In the Sahellan zone, In the result of decrease In the frequency of rainy days and not due to any significant change In the rainfall intensity.